The Educated Class and the Fragility of Consumer Society - Gilles Saint-Paul (Institute of Labor Economics (IZA), 2025)
We analyze the importance of the educated class for the persistence of mass consumption societies in an economy with a hierarchy of needs.Through the demand for managerial talent (which is needed to operate advanced industrial technologies), the latter generate their own demand for skills. In turn, high wages for skilled labor raise the demand for a broad range of industrial products. Thus, mass consumption society is self-sustaining but may also collapse. An increase in the managerial labor requirement, while a form of technical regress, may sustain a high skilled wage, high industrialization, equilibrium. In the dynamic analysis, a collapse of mass consumption society may be triggered after the economy has accumulated a critically high level of human capital. Following a collapse, the educated class disappears but gradually recovers as its own scarcity ignites a positive feedback loop between the demand for skills and the income of skilled workers. But collapses may happen again, and the economy may experience cycles.
Keywords: 330; Soziale Schicht; Bildungsniveau; Privater Konsum; Fachkräfte; Konsumentenverhalten; Konsumgesellschaft; Theorie